2012
DOI: 10.1056/nejmoa1207285
|View full text |Cite
|
Sign up to set email alerts
|

Cord-Blood Engraftment with Ex Vivo Mesenchymal-Cell Coculture

Abstract: BACKGROUND Poor engraftment due to low cell doses restricts the usefulness of umbilical-cord-blood transplantation. We hypothesized that engraftment would be improved by transplanting cord blood that was expanded ex vivo with mesenchymal stromal cells. METHODS We studied engraftment results in 31 adults with hematologic cancers who received transplants of 2 cord-blood units, 1 of which contained cord blood that was expanded ex vivo in cocultures with allogeneic mesenchymal stromal cells. The results in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
390
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(409 citation statements)
references
References 32 publications
5
390
0
7
Order By: Relevance
“…One strategy has been focused on the ex vivo expansion of HSPC prior to transplantation which has now been tested in several clinical trials (Pineault and Abu-Khader 2015;Norkin et al 2013;Delaney et al 2005;Cairo et al 2016;de Lima et al 2012). Indeed, decreased graft failure and accelerated neutrophil recovery have been reported in patients undergoing double CB transplantation with an expanded and unmanipulated units, each unit providing short-and long-term engraftment, respectively (de Lima et al 2012;Delaney et al 2010;Horwitz et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One strategy has been focused on the ex vivo expansion of HSPC prior to transplantation which has now been tested in several clinical trials (Pineault and Abu-Khader 2015;Norkin et al 2013;Delaney et al 2005;Cairo et al 2016;de Lima et al 2012). Indeed, decreased graft failure and accelerated neutrophil recovery have been reported in patients undergoing double CB transplantation with an expanded and unmanipulated units, each unit providing short-and long-term engraftment, respectively (de Lima et al 2012;Delaney et al 2010;Horwitz et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Still, expansion of the true hematopoietic stem cell pool has been limited 2, 4, 45, 46. We 4, 5, 6, 7 and others 38 have previously shown that CB‐HSPC can be effectively expanded and driven to differentiate toward both the myeloid and lymphoid lineages in a serum‐free culture system, using a feeder layer of adult human BM‐derived stromal cells. Using this system, we have optimized initial progenitor content and cytokine concentrations 7, 8, 9, and demonstrated that the expanded human CB‐HSPC had the ability to engraft pre‐immune fetal sheep 5.…”
Section: Discussionmentioning
confidence: 90%
“…The first attempts at ex vivo expansion of CB‐HSPC used growth factors alone, and led to inadequate outcomes. However, when patients were transplanted with HSPC that had been cocultured in the presence of supportive stromal layers, the time to neutrophil and platelet reconstitution was significantly shortened 38. Other approaches to expand the numbers of transplantable HSPC within a unit of CB have included or involved activation of endogenous Notch receptors 39, nicotinamide analogs 40, aryl hydrocarbon receptor antagonists 41, copper chelators 1, histone deacetylase inhibitors 42, and engraftment enhancers such as PEG2 43 and CXCR4 44.…”
Section: Discussionmentioning
confidence: 99%
“…Double cord blood transplantation has been extensively investigated but, to date, a survival advantage has not been shown over single UCB units or unrelated donor grafts 7,28-37 and additional efforts are being investigated in clinical trials. 4,38,39 As these attempts are explored and potentially practice-changing data emerges, improvements and expertise in our current transplant procedures are of great importance.…”
Section: Discussionmentioning
confidence: 99%